A.O. Olukoshi og L. Laakso (red.), Challenges to the Nation-State in Africa, Uppsala: Nordiska Afrikainsitutet og Motala: University of Helsinki, The Institute of Development Studies, 1996, 213 s, SEK 180,00. - Hvenegård-Lassen, Kirsten (Politica, 1996)
-